1970
DOI: 10.1080/00288233.1970.10421595
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic use of calcined christmas island iron/aluminium phosphates i. field trials

Abstract: Christmas Island "c" ore when calcined at 550°c contains up to 24% aluminium and iron and 15% phosphorus which is not water-soluble but is up to 95% soluble in neutral ammonium citrate. Samples vary in total phosphorus content and in the percentage of phosphorus soluble in neutral ammonium citrate, depending on the proportions of crandallite, millisite, and apatite in the "c" ore sample. In field trials at Otara finely ground calcined "c" ore-"Calciphos"-gave yields equal to or slightly less than those obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
2

Year Published

1979
1979
1988
1988

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 6 publications
(4 reference statements)
1
8
0
2
Order By: Relevance
“…They suggested that 10% bentonite may be necessary for breakdown to give satisfactory plant responses. Buchan et al (1970) confirmed in pot trials that only pellets with 10% bentonite disintegrated completely in the soil, and Muller (1970) reported that, in a field trial, pelletised Calciphos with 8% bentonite gave pasture yields of 61% of those obtained from superphosphate. However, at that time, the higher cost of producing bentonite pellets relative to the lower cost of phosphate rock was not considered economical.…”
Section: Introductionsupporting
confidence: 58%
“…They suggested that 10% bentonite may be necessary for breakdown to give satisfactory plant responses. Buchan et al (1970) confirmed in pot trials that only pellets with 10% bentonite disintegrated completely in the soil, and Muller (1970) reported that, in a field trial, pelletised Calciphos with 8% bentonite gave pasture yields of 61% of those obtained from superphosphate. However, at that time, the higher cost of producing bentonite pellets relative to the lower cost of phosphate rock was not considered economical.…”
Section: Introductionsupporting
confidence: 58%
“…Although oflittle agronomic value in the raw state, calcination at 550·C increases the agronomic performance of this material. Calciphos has been evaluated extensively in both the glasshouse and the field in New Zealand (Doak et al 1965;Buchan et al 1970;Muller 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Nauru Island rock phosphate was considerably less effective, Doak et al (1965) showed that C-grade Christmas Island rock phosphate, which contains crandallite and millisite as well as apatite and is unsuitable for the manufacture of superphosphate by conventional means, could be calcined at about 450"c with resultant degradation of the crystal lattices and enhanced solubility of the phosphate content. Although Muller (1970) and Buchan et at. (1970) found that this finely ground CCIP gave yields equal to or slightly less than superphosphate in field and pot experiments, Elliott (1967) concluded from results offield trials carried out by the New Zealand Department of Agriculture that CCIP was only half as effective as superphosphate when compared on an equal phosphate content basis.…”
Section: Introductionmentioning
confidence: 94%
“…This discrepancy would appear to be associated with the application rate and the position on the phosphate response curve at which the materials were compared. On closer examination, Muller's (1970) Karlovsky (1976) compared CCIP with superphosphate (annual applications on an equal phosphate basis) in a 5-year trial on permanent pasture on Horotiu sandy loam (a highly phosphate retentive yellow-brown loam). Although the yield from CCIP in the first year was only 41% ofthe yield from superphosphate, it improved with time, and by the fifth year it yielded 84% as much as superphosphate.…”
Section: Introductionmentioning
confidence: 99%